Human Capital and Sustainable Teacher Performance: Examining the Impact of Servant Leadership, Competence, and Professional Commitment in Catholic Education - Budiyanto, Hendro; Djati, Sundring Pantja; Alirejo, Mohamad Subroto; Rini, Wahju Astjarjo (Journal of Applied Data Sciences, 2025)
This study examines the impact of servant leadership on the performance of Catholic religious teachers, with competence and professional commitment as mediating variables. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 151 Catholic religious teachers in the Jakarta Archdiocese. The results show that servant leadership has a direct positive impact on teacher performance (β = 0.317, p 0.001) and indirectly enhances performance through competence (β = 0.199, p = 0.008) and professional commitment (β = 0.186, p = 0.002). Competence (β = 0.357, p = 0.001) and professional commitment (β = 0.340, p = 0.002) significantly improve teacher performance. The structural model explains 74.9% of the variance in teacher performance, indicating strong predictive power. This study contributes to the literature by demonstrating the mediating role of competence and professional commitment in the relationship between servant leadership and performance, particularly in Catholic education. The findings provide practical implications for school administrators and policymakers to implement servant leadership strategies that enhance teacher competence and commitment. This research introduces a comprehensive approach to improving teacher effectiveness in religious education settings, emphasizing the importance of leadership styles that prioritize service, empowerment, and professional development.